Znatkova O.M. Facilitation as participative technology in public administration system in Ukraine - admin, admin (Pressing Problems of Public Administration, 2019)
The present-day challenges require specific quality changes in the public administration system of Ukraine. Even now we can indicate certain positive shifts in the field, in particular, those in the relations of the state with the civil society e.g. the development of the regulatory framework for encouragement of the participativity concept (public participation) as a true manifestation of democratic rule, systemic and effective involvement of citizens in the state formation process. However, today this concept still remains inefficient in practical terms for a number of reasons: outdated forms and methods of interaction between the authorities and the society; authoritarian approach; old-time traditions; and what is most significant, the society needs to be aware of the relevant technologies to understand the importance of personal engagement in administering of political processes.